The Effect of The Use of AI on Creativity in Creative Companies - Hamza Bami; Yang Jing Zhao; Zhu Xun; Muneeb Ali (Journal of Information Systems Engineering and Business Intelligence, 2026)
Background: The rapid use of artificial intelligence (AI) in the creative industries has raised some questions about whether it will have any effects on human creativity and innovative practices. Recent studies highlight the possibility of AI to enhance creative output and the impact of originality and human agency. Objective: This study uses the technology acceptance model (TAM) to assess the role played by the implementation of AI in the creative process in creative companies. The role of perceived usefulness, perceived ease of use, behavioral intention to use AI, and trust in AI as a moderating variable is investigated. Methods: The study was based on a quantitative methodology, where data were collected from 720 creative companies in China. A well-designed questionnaire based on the literature was sent to the professionals, and the data were analyzed. The proposed relationships were analyzed with the help of SmartPLS. Results: Preliminary results show that perceived usefulness and ease of use positively contribute to employee attitudes toward AI, which, in turn, positively impact their intention to use AI and eventually lead to high levels of creativity. However, trust in AI had no significant effect in moderating the relationship between attitude toward using and behavioral intention. Conclusion: These findings indicate that the development of positive attitudes toward AI and its adoption can lead to the enhancement of creativity in an organization that works in a highly innovative industry. This study contributes to the growing literature on AI and creativity and offers practical implications for managers and policymakers who plan to use AI as a creative performance tool. Further studies can also be based on these findings to explore other variables, additional contexts, and long-term outcomes to expand the knowledge of AI’s role in forming creativity.   Keywords: Artificial intelligence (AI), Technology Acceptance Model (TAM), Creative industries, Creativity, PLS-SEM